Loneliness, Hopelessness, and Meaning in Life among Young Adults Following a Romantic Breakup - Hanhan Muhammad Doddy; Rifqi Farisan Akbar; Prinska Damara Sastri (Training & Research Institute - Jeramba Ilmu Sukses, 2026)
This study examined the relationships and predictive contributions of loneliness and hopelessness to meaning in life among young adults following a romantic breakup. A quantitative correlational design was employed using an online questionnaire distributed to individuals aged 20–25 years who had experienced the end of a romantic relationship lasting at least six months. Of the 81 responses received, 67 met the eligibility criteria and were included in the analysis. Data were analyzed using Pearson’s correlation, multiple linear regression, and supplementary analyses of the Presence of Meaning and Search for Meaning dimensions. The results showed that loneliness was negatively associated with meaning in life, although it did not make a significant unique contribution when hopelessness was included in the regression model. Hopelessness, in contrast, emerged as a significant negative predictor and the strongest variable in the model. Together, loneliness and hopelessness explained 49.2% of the variance in meaning in life. Additional findings indicated that hopelessness was more strongly related to the Presence of Meaning than to the Search for Meaning. These results suggest that meaning in life after a romantic breakup is more closely associated with hope, future orientation, and confidence in the possibility of a better life than with loneliness alone